Leptin Maintained Zinc Homeostasis Against Glutamate-Induced Excitotoxicity by Preventing Mitophagy-Mediated Mitochondrial Activation in HT22 Hippocampal Neuronal Cells - Jin, Mei-fang; Ni, Hong; Li, Li-li (Frontiers in Neurology, 2018)
Developmental seizure-induced long-term neuronal hyperexcitation is partially mediated by regenerative mossy fiber sprouting in hippocampus. Yet, there are no effective drugs available to block this pathological process. Recently, leptin has been shown to prevent the sprouting of hippocampal mossy fibers and abnormalities in the neurobehavioral parameters. However, their underlying molecular mechanisms are largely unknown. The purpose of this study was to determine the effect of glutamate on the parameters of zinc homeostasis, mitochondrial functions and mitophagy regulating factors, as well as to investigate the protective effects of leptin against cytotoxicity of glutamate in murine HT22 hippocampal neuronal cells. Cells were assigned to one of four groups as follows: control group, leptin alone group, glutamate injury group and leptin pretreatment group. Our results demonstrated that glutamate induced a decrease in SOD (superoxide dismutase), GSH (glutathione), mitochondrial membrane potential and an increase in GSSG (oxidized glutathione), mitochondrial ROS, and supplementation of leptin blocked the toxic effect of glutamate on cell survival. The glutamate-induced cytotoxicity was associated with an increase in mitophagy and intracellular zinc ion levels. Furthermore, glutamate activated the mitophagy markers PINK1, Parkin and the ratio of LC3-II/LC3-I, as well as increased the expression of ZnT3. Leptin corrected these glutamate-caused alterations. Finally, the mitophagy inhibitor, CsA, significantly reduced intracellular zinc ion content and ZnT3 expression. These results suggest that mitophagy-mediated zinc dyshomeostasis and mitochondrial activation contributed to glutamate-induced HT22 neuronal cell injury and that leptin treatment could counteract these detrimental effects, thus highlighting mitophagy-mediated zinc homeostasis via mitochondrial activation as a potential strategy to counteract neuroexcitotoxicity.